Promising Co/NC nanocomposite electrode material derived from zeolitic imidazolate framework for high performance and durable aqueous symmetric supercapacitor. (December 2020) - Bharti, Abha; Thangavel, Ramesh; Natarajan, Rajalakshmi
Highlights: Dual zeolitic imidazolate framework precursor derived Co/NC electrode material. Rational combination of metal, nitrogen, and carbon through dual precursor approach. No usage of any additional carbon sources and/or post treatment process. Co/NC//Co/NC supercapacitor with high capacitive performance and cyclic stability. Better cyclic stability than state-of-art activated carbon electrode materials. Abstract: Cobalt incorporated nitrogen doped carbon (Co/NC) nanocomposite is prepared via single step direct carbonization of dual Zeolitic Imidazolate Framework (ZIF) precursors, Zn-ZIF and Co-ZIF without any additional precursors and/or processing steps. Benefiting from the rational combination of metal, nitrogen and carbon through dual precursor approach, the derived Co/NC nanocomposite exhibited porous graphitic structure and high surface area (415 m 2 g −1 ) along with good wettability. Such amalgamation of properties favours facile migration of electrons and ions resulting in improved capacitance. The electrochemical capacitive properties of Co/NC nanocomposite as electrode material for supercapacitors (SCs) is evaluated in both three-electrode and two-electrode system with 6 M KOH as the electrolyte. Co/NC nanocomposite exhibited typical electrochemical double layer capacitive behaviour and showed a specific capacitance of 195 F g −1 (at 1 A g −1 ) along with good rate capability in three-electrode system displaying its potential for SC applications. Furthermore, Co/NC//Co/NC SC device demonstrated maximum energy density and power density of 9.8 W h kg −1 and 6.7 kW kg −1, respectively. Co/NC//Co/NC SC device also exemplified good cycling stability with 85% capacitance retention after 5000 cycles of galvanostatic charge/discharge at 2 A g −1 . The results substantiate the applicability of Co/NC nanocomposite for electrochemical energy storage applications.